Respostas
respondido por:
1
x - y = 7
x + y = 3 +
‾‾‾‾‾‾‾‾‾‾
2x = 10
x = 10/2
x = 5
x + y = 3
5 + y = 3
y = 3 - 5
y = - 2
S = {5,- 2}
x + y = 3 +
‾‾‾‾‾‾‾‾‾‾
2x = 10
x = 10/2
x = 5
x + y = 3
5 + y = 3
y = 3 - 5
y = - 2
S = {5,- 2}
respondido por:
1
X-y=7
X+y=3
X-y=7
X=7+y
X+y=3
7+y+y=3
2y=3-7
2y=-4
Y=-4/2=-2
X+y=3
X-2=3
X=3+2
X=5
Espero ter ajudado
X+y=3
X-y=7
X=7+y
X+y=3
7+y+y=3
2y=3-7
2y=-4
Y=-4/2=-2
X+y=3
X-2=3
X=3+2
X=5
Espero ter ajudado
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás